A Proposed Method to Find Exciter’s Maximum Acceleration Magnitude on Vibration Meter Calibration System - Ninuk Ragil Prasasti; Denny Hermawanto (Instrumentasi, 2020)
National Measurement Standards-National Standardization Agency of Indonesia (SNSU-BSN) has implemented calibration method for vibration meters according to ISO 16063-21:2003. In this calibration system, an electrical signal at a particular frequency and magnitude is generated by the signal generator. Then it is amplified before converted into a mechanical vibration by the exciter. A vibration acceleration produced by the exciter is measured by the reference accelerometer as well as the vibration meter under test simultaneously. However, the maximum acceleration generated in the calibration system is affected and limited by several factors such as a total mass load of accelerometer, data acquisition system, displacement and velocity limits of an exciter. This paper presents the analysis of maximum acceleration produced by the exciter in the vibration meter calibration system considering the effect of those factors within a frequency range from 10 Hz to 5 kHz.